ANALISIS TEKS RETORIKA TAJUK RENCANA PADA SURAT KABAR KOMPAS EDISI JANUARI 2017 - Dina Putri Juni Astuti (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2018)
The purpose of this research is to find out the text of rhetoric on: (1) structure of editorial text of Kompas newspaper of January 2017 edition (2) word choice (diction) in editorial in Kompas newspaper January 2017 edition and, (3) language style in editorial Kompas daily newspaper January 2017 edition. This research method is descriptive method with qualitative approach. The source of research data in the form of a newspaper compass edition januari 2017. While the data in the form of editorial text in Kompas daily newspaper edition of January 2017 amounted to 25 texts editorial. Data analysis uses text structure theory and word choice according to Bolivar and style of language according to Koesworo. The results show that (1) the editorial rhetoric text on the text structure of Kompas newspaper has five types of text structure variation. The five variations are SDR-SDR-SDR, SD-SDR-SDR, SDR-SDR-SD, SD-SDR-SD and SDR-SD-SD. This pattern variation is based on the location of the Triad position (S representative situation, D development representative, and R representative of the recommendations) contained in each editorial text. (2) Editor's choice of wording in Kompas newspaper, all 25 data use the word choice that has been grouped by Bolivar, ie the form of the word adverb, the word modality and the lexical word form. In general, the more widely used group of word choices is the lexical word in the noun. And (3) editorial style language in Kompas newspaper, all 25 data have suggestive language style, analytical logic and literary. In general, the more widely used language style is the analytical logical language style which is the style of the form of a form of thinking created by the author for the reader to consider the author's opinion on the issues discussed so that the reader will gain a logical reason from the reader's own mind.Keywords: Text, Rhetoric, and Editorial